2021
DOI: 10.1016/j.ssmph.2021.100845
|View full text |Cite|
|
Sign up to set email alerts
|

Overcrowding and COVID-19 mortality across U.S. counties: Are disparities growing over time?

Abstract: A growing line of research underscores that sociodemographic factors may contribute to disparities in the impact of COVID-19. Further, stages of disease theory suggests that disparities may grow as the pandemic unfolds and more advantaged areas are better able to apply growing knowledge and mitigation strategies. In this paper, we focus on the role of county-level household overcrowding on disparities in COVID-19 mortality in U.S. counties. We examine this relationship across three theoretically important peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
(54 reference statements)
2
20
0
Order By: Relevance
“…For instance, region-based research has shown that county-level factors are associated with physical distancing behaviors. Counties with more health-protective behaviors prior to the pandemic (e.g., less obesity, greater physical activity) exhibited a greater reduction in movement outside of the home compared to counties with fewer health-protective behaviors [ 20 ], and counties with higher rates of poor housing conditions (e.g., overcrowding) have more COVID-19 deaths [ 57 ]—suggesting that an inability to distance from others may explain the increased incidence of COVID-19. There is also evidence showing that high SES individuals were more likely to engage in physical distancing behaviors compared to low SES individuals [ 3 , 22 , 36 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, region-based research has shown that county-level factors are associated with physical distancing behaviors. Counties with more health-protective behaviors prior to the pandemic (e.g., less obesity, greater physical activity) exhibited a greater reduction in movement outside of the home compared to counties with fewer health-protective behaviors [ 20 ], and counties with higher rates of poor housing conditions (e.g., overcrowding) have more COVID-19 deaths [ 57 ]—suggesting that an inability to distance from others may explain the increased incidence of COVID-19. There is also evidence showing that high SES individuals were more likely to engage in physical distancing behaviors compared to low SES individuals [ 3 , 22 , 36 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited language proficiency and cultural know-how may also preclude immigrants, particularly recent arrivals, from engaging with the provincial vaccine booking system. Third, these groups more often reside in overcrowded households and dense neighborhoods with fewer health-promoting amenities such as access to family physicians and pharmacies (Bambra et al 2020; Choi and Denice 2020; Kamis et al 2021; Krieger et al 2020; Yang et al 2020). Limited access to health care may mean that racial minorities and low-income individuals have to travel long distances or wait long periods to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has exposed how NPIs such as social distancing are structured by economic and racial advantage. In the context of an emerging infection, these effects may be even more acute than with many noncommunicable diseases: While more-advantaged individuals wait out infection at home, the response evolves, clinical management of infection improves, and case-fatality rates fall, allowing these groups to sidestep the worst effects almost entirely, while minoritized and poorer groups take the brunt of infection and death [ 4 , 57 ]. Including mechanisms of social and economic dependence in exposure , i .…”
Section: Protective Npis Policies and Medical Innovations Reach More-...mentioning
confidence: 99%